2014
DOI: 10.1002/jcla.21696
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Quantitative Gel Zymography for Matrix Metalloproteinases

Abstract: Analytical parameters of zymography were suitable for detection of MMPs in human plasma. Quantitative zymography for MMPs is an alternative method for comparing the results of ELISA widely employed for MMP determination, thus reducing the discrepancies between laboratories regarding gelatinase assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…As in previous reports, we found a strong correlation ( r = 0.81) between MMP-9 active and total form measured, respectively, by gel zymography and ELISA 38 , 39 . However, the Pearson’s correlation coefficient ( r ) does not assess agreement between the two methods but rather measures the association between them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in previous reports, we found a strong correlation ( r = 0.81) between MMP-9 active and total form measured, respectively, by gel zymography and ELISA 38 , 39 . However, the Pearson’s correlation coefficient ( r ) does not assess agreement between the two methods but rather measures the association between them.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, Prescimone et al, compared both methods in 25 volunteers using correlation coefficient and Bland–Altman difference analysis. Based on the correlation coefficient and regardless of the absolute systematic error (0.006 mg/l) revealed by Bland–Altman analysis, they concluded that both methods offer similar reliability for quantifying MMP-9 38 . In accordance with their results, we obtained a positive bias between gel zymography and ELISA, but on a significant larger scale (0.11 mg/l).…”
Section: Discussionmentioning
confidence: 99%
“…The zymography is a reproducible and reliable method to detect gelatinase activity (Prescimone et al, ). It is based on sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) with the 0.5% gelatin (type A from porcine skin, Sigma‐Aldrich, St Louis, MO) as substrate for detection of MPs enzymatic activity.…”
Section: Methodsmentioning
confidence: 99%
“…The use of MMP and TIMP plasma levels as biomarkers in different clinical settings is increasing due to their diagnostic and prognostic value in human medicine (23,27). Currently, only a few studies have been focused on plasma or milk levels of MMP (21,28), while the plasma level of TIMPs in cattle is lack of relevant research.…”
Section: Discussionmentioning
confidence: 99%